Expression of Fibronectin and Matrixmetalloproteinase-1(MMP-1) In Breast Cancer Patients in Basrah Province - Zainab Abdul-Wahid Shayea; Dhamia Kasim Suker; Saad Abdalbaqi Abdullah (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Fibronectin is an extracellular matrix protein that is expressed in almost all types of cancers and plays a crucial role in tumor growth promotion, survival and resistance to therapy. Matrix metalloproteinases (MMPs) are a family of enzymes implicated in the degradation and remodeling of extracellular matrix and in vascularization. The present study involved 82 samples including 57 patients of breast cancer and 25 as control (breast benign tumor). When the ELISA levels of MMP-1 in cancer patients were compared to its levels in benign tumor patients, it was noticed that the levels in cancer patients were significantly statistically higher than the levels in benign tumor patients. No such significance could be noticed when ELISA FN was tested. The comparison, of ELISA MMP-1 and ELISA FN in cancer patients sub-grouped according to type, stage, and grade of the tumor, shows that there are differences in the measures of central location and measures of dispersion. Results showed there was no any significant statistical difference in the presence of IHC MMP-1 and the presence of IHC FN between both groups, cancer and benign tumor patients. The IHC MMP-1 presence in cancer patients was investigated according to the characteristics of the malignancy, type, stage, and grade and no conclusive results could be elicited. Also, when the IHC FN presence in cancer patients was investigated according to the characteristics of the malignancy, type, stage, and grade, again no conclusive results could be elicited.